2016
DOI: 10.3945/ajcn.116.130542
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of a cranberry juice beverage lowered the number of clinical urinary tract infection episodes in women with a recent history of urinary tract infection

Abstract: The consumption of a cranberry juice beverage lowered the number of clinical UTI episodes in women with a recent history of UTI. This study was registered at clinicaltrials.gov as NCT01776021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 39 publications
1
53
0
7
Order By: Relevance
“…This reduction corresponded to a reduction of nearly half the frequency of cystitis in the first 3 months (46.2%) and an incidence ratio of 0.59 compared to placebo. This finding is comparable to the incidence ratio calculated in the Cochrane review [12] in 2008 based on 10 clinical studies (relative risk [RR] 0.65, 95% CI 0.46-0.90) [13] and also comparable to the recent Maki et al [14] study (RR 0.62, 95% CI 0.42-0.92). Another meta-analysis of 13 trials postponed the protective effect of cranberry consumption against recurrence of cystitis by 0.53 (95% CI 0.33-0.83) [15].…”
Section: Discussion/conclusionsupporting
confidence: 74%
See 1 more Smart Citation
“…This reduction corresponded to a reduction of nearly half the frequency of cystitis in the first 3 months (46.2%) and an incidence ratio of 0.59 compared to placebo. This finding is comparable to the incidence ratio calculated in the Cochrane review [12] in 2008 based on 10 clinical studies (relative risk [RR] 0.65, 95% CI 0.46-0.90) [13] and also comparable to the recent Maki et al [14] study (RR 0.62, 95% CI 0.42-0.92). Another meta-analysis of 13 trials postponed the protective effect of cranberry consumption against recurrence of cystitis by 0.53 (95% CI 0.33-0.83) [15].…”
Section: Discussion/conclusionsupporting
confidence: 74%
“…We found no other references to this clinically important improvement. Maki et al [14] who investigated the time to first recurrence did not showed such results. The results of in vitro and in vivo studies suggest that cranberry interferes with the adherence of uropathogenic E. coli to the epithelial cells of the bladder, periurethral region, and intestinal tract [17][18][19][20].…”
Section: Discussion/conclusionmentioning
confidence: 81%
“…Several clinical trials have showed the beneficial effects of cranberry intake on human health [1,2,3,4,5,6,7]. However, while in vitro studies have shown dose-response effects of cranberry (poly)phenols on the inhibition of microbial invasion of gut and bladder epithelial cells [8,9] and in the cytotoxicity of ovarian cancer cells [10], very few human dose-response studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The antiadhesion effect of cranberry is attributed to its high molecular mass constituents (Sobota 1984;Ofek et al 1996;Burger et al 2000;Weiss et al 2002). Likewise, many recent clinical studies proved the efficiency of cranberry in prevention of UTIs (Maki et al 2016;Fu et al 2017;Nabavi et al 2017;Thomas et al 2017). This study did not report bactericidal activity towards planktonic ( inflating the balloon, were evaluated.…”
Section: Discussionmentioning
confidence: 99%